Evaluasi Pelaksanaan Program Jam Ekatra Layanan Administrasi (Jelita) di Kecamatan Dringu Kabupaten Probolinggo - Verto Septiandika; Andini Kurdianingtiyas (Mahesa Research Center, 2022)
This paper aims to evaluate the implementation of the Jelita program (Extra Hours for Administrative Services) in Dringu District, Pobolinggo Regency. So that problems arise that are focused on How to Implement Jelita (Extra Hours of Administrative Services) in Dringu District, Probolinggo Regency and have advantages and disadvantages in implementing the Jelita Program (Extra Hours of Administrative Services) in Dringu District, Probolinggo Regency''. To solve this problem use the theory of William Dunn. So this research data obtained from observations, interviews, interviews. This study uses a descriptive qualitative method with a case study approach in Dringu District. The results of the study suggest that an evaluation of the implementation of the Jelita program (Extra Hours for Administrative Services) in Dringu District, Probolinggo Regency is carried out through 6 policy evaluation criteria including effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. Evaluation of program implementation has gone well from the 6 policy evaluation criteria. The supporting factors for the implementation of the Jelita Program are good communication and quality resources. While the inhibiting factors for the implementation of the Jelita Program are internal factors in the form of internet network stability and system errors in the SIAK application.